Mobile hotspots and refugia of avian diversity in the mountains of south‐west China under past and contemporary global climate change. (27th September 2016) - Wu, Yongjie; DuBay, Shane G.; Colwell, Robert K.; Ran, Jianghong; Lei, Fumin
Abstract: Aim: To identify hotspots of endemic and non‐endemic avian diversity in the mountains of south‐west China and delineate biodiversity corridors that connect the faunas of northern and southern Asia. To understand how biodiversity and endemism in this region has been maintained through palaeoclimate change. Location: The mountains of south‐west China, spanning an elevational gradient > 7000 m. Methods: We used the distributional data of 752 breeding birds to investigate current patterns of diversity across elevational and geographical space. We simulated species richness under palaeoclimate models of global temperature change, assessing changes in species richness. Results: Contemporary species richness of non‐endemic birds peaked at 800–1800 m elevation, while endemic richness peaked at 2000–3000 m. Richness of non‐endemic birds was highest in the southern Hengduan Mountains and Yungui Plateau, while endemic richness peaked further north, extending into the mountains along the western edge of the Sichuan Basin. Under global warming models, species richness remained high throughout the Hengduan Mountains region. Under global cooling models, the Sichuan Basin showed increased richness. Conclusions: Endemism peaked in the mountains along the western edge of the Sichuan Basin, highlighting the importance of this region in promoting and maintaining diversity. This region has likely functioned as a biodiversity corridor, bridging the Palaearctic and Oriental biotas to the north and south. Climate simulations suggest that the mountains of south‐west China can accommodate upslope range shifts in response to warming, but low elevation specialists may have experienced increased extinction probabilities during cold periods in the recent past, which may in part explain the current mid‐elevation diversity peak. During glacial periods the Sichuan Basin likely served as a warm refugium for montane birds. Steep environmental heterogeneity has been a key to maintaining high diversity and endemism in the region during palaeoclimate change. These same features will likely shape the effects of future climate change on biodiversity in the region.